In Situ Bioremediation Strategies for the Recovery of Mercury-contaminated Land in Abandoned Traditional Gold Mines in Indonesia - Winardi Winardi; Eko Haryono; Sudrajat Sudrajat; Endang Sutariningsih Soetarto (Biosaintifika: Journal of Biology & Biology Education, 2020)
Traditional gold mining activities release mercury into the environment, creating a major concern for the Indonesian governments today. In situ bioremediation, which draws on the activities of indigenous soil bacteria for the recovery of mercury-contaminated land, has never been conducted intensively in the country. This research set out to determine the most efficient in situ bioremediation strategy for this purpose. It took place in Mandor Village, Landak Regency, Kalimantan Barat-Indonesia. During the experiment, four groups of sampling plots were made into triplicate and given various treatments: a. nutrient addition, b. aeration, c. pH neutralization, and d. without nutrient addition and aeration as a control. pH neutralization was conducted in all sampling plots by adding lime until soil pH of ±7 was achieved. The experiment was performed during both rainy and dry seasons to determine the influence of seasonal weather. Total mercury levels of each plot were measured on day 0, 30, 60, 90, and 120, and the effects of treatments and time on mercury depletion were analyzed by two-way ANOVA (P0.05), followed by a post hoc test to identify the best treatment and optimum time for in situ bioremediation. The results showed that the best time to conduct this bioremediation was in the rainy season by applying nutrient addition and aeration for 90 days on soils with neutral pH; these stimulations could remove ±89.6% of the mercury. This bioremediation technique is a novel technological approach in land recovery that local governments can adopt to restore soils contaminated with mercury from traditional gold mining.